Mineral and ore characterization of the rare earth element from Khotgor deposit - G, Burmaa; S, Alen; T, Аzzaya (Bulletin of the Institute of Chemistry and Chemical Technology, 2018)
Although many new deposits of rare earth elements (REEs) are being discovered, the technical and technological knowledge on the separation of REEs from its ore by concentrating procedure and concentrate treatment are limited. In Mongolia, doing research on the chemical technological characteristics of the REEs mineral and ore would have been a great importance for the academic research knowledge and creation of new documents with respect to REEs. Moreover, it can be efficiently resulted to socio-economic issue in our country. The surface rocks and ore from Khotgor deposit located in Umnugobi province were studied by electron microscopy, SEM/EDX and X-ray diffraction method. As a result, the rocks are composed to sienite protracted by carbonatite, nepheline-sienite rocks with breccially-formed, apatite (flourapatite) with 1-3%, barite, celestine, pyrite and magnetite, respectively. In the rock, REEs’s total content was about 0.02-1.6%, and its 86.2-95.7% for the cerium group elements. A nepheline sienite and sienite that includes apatite, barite, celestine, pyrite and magnetite were composed to the ore. Total content of REEs in this ore was 2.18% with light REEs about 95%. This study summarized the chemical composition of rocks, ores and minerals. Furthermore, the contents of REEs and characterization of the carrier minerals and other accompanied minerals were presented. Хотгор ордын газрын ховор элементийн хүдэр ба эрдсийн шинж чанар Хураангуй: Газрын ховор элемент (ГХЭ)-ийн олон шинэ ордууд нээгдэж байгаа ч тэдгээрийн хүдрээс ГХЭ-ийг баяжуулан ялгаж авах, баяжмалыг боловсруулах техник технологийн мэдлэг хязгаарлагдмал байгаа өнөө үед Монгол улс дахь ГХЭ-ийн хүдэр, эрдсийн химийн технологийн шинж чанарыг нарийвчлан судалж, академик судалгааны мэдлэг хуримтлуулах, баримт материал бий болгох нь нийгэм, эдийн засгийн чухал ач холбогдолтой. Өмнөговь аймгийн нутагт орших Хотгор ордын гадаргын чулуулаг ба хүдрийг электрон микроскоп, SEM/EDХ ба рентген дифракцийн аргаар судлав. Чулуулаг нь гадаргуугийн өгөршилд өртсөн сиенит ба брекчлэг бүтэц үүсгэсэн нефелин сиенит чулуулгаас тогтсон, сиенит нь карбонатитээр бага зэрэг түрэгдсэн 1-3% хүртэл апатит (фторапатит) болон барит, целестин, пирит, магнетит зэрэг эрдэс агуулж байна. Чулуулагт ГХЭ-ийн нийлбэр агууламж 0.02-1.6%, түүний 86.2-95.7% нь церийн бүлгийн элементүүдэд ноогдоно. Хүдрийн чулуулаг нь апатит (фторапатит) болон барит, целестин, пирит, магнетит зэрэг эрдэс агуулсан сиенит ба нефелин сиенит, ГХЭ-ийн нийлбэр агууламж 2.18%, мөн түүний 95%-ийг хөнгөн ГХЭ-үүд эзэлж байна. Энэхүү судалгаанд чулуулаг, хүдэр, эрдсүүдийн химийн бүрдэл, ГХЭ-ийн агууламж, тээгч ба дагалдах зарим эрдсүүдийн шинж чанарыг судалсан үр дүнгээс оруулав. Түлхүүр үг: нефелин,сиенит, апатит, фторапатит